Literary Narratives of the Past: Generations of Memory and Everyday Life Under the Romanian Communist Regime. (3rd July 2018) - Mitroiu, Simona
ABSTRACT: In Romania, the literary approach to the recent communist past centred on everyday life under the communist regime is usually associated with a nostalgic communist perspective. By reading communist nostalgia in the context of the communist politics that pervaded every aspect of everyday life, this paper traces the connections between narratives and moral responsibility at the level of Romanian literary productions. Many of the topics included in the collective volumes that bring together personal narratives of the past resonate with and influence the fictional creations of the past; in many cases, combining personal testimonies with fictional characters offered an improved mechanism for dealing with the past. The paper argues that the topic of daily life experiences under the communist regime can be further developed, raising awareness of the lack of discussions about moral responsibility at the societal level in post-totalitarian Romania. Even if the younger generations can use the literary narratives of the past to re-appropriate their predecessors' life stories, the reduction of the past to visual or linguistic stereotypes deepens the separation between public and private memory.